Dynamic logic : new trends and applications : first International Workshop, DALI 2017, Brasilia, Brazil, September 23-24, 2017, Proceedings /: new trends and applications : first International Workshop, DALI 2017, Brasilia, Brazil, September 23-24, 2017, Proceedings. (2018) - Unknown
No abstract available